The problem of developing a model for the settlement Transnistrian conflict in the context of European integration of the Republic of Moldova - Anatolii Dirun; Valentina Teosa (CES Working Papers, 2023)
The participation of the European Union in the settlement of the Transnistrian conflict created favorable conditions for the implementation of the concept of "involvement without recognition" of the Transnistrian region in the legal field of the Republic of Moldova. The effectiveness of this approach largely depended on the effective functioning of the EU as an intermediary and the tools used to solve this problem. The purpose of the work is to consider the influence of the "post-military" stage on the effectiveness of the implementation of the mediation activities of the European Union, as well as to analyze the strategy of "Europeanization" from the point of view of rational choice theory, which affects the change in the behavior of the conflicting parties in the context of the settlement of the Transnistrian conflict.
Keywords: 330; Transnistrian conflict; Europeanization strategy; post-war stage; conflict transformation